Edukasi Demensia Sebagai Bentuk Pelibatan dan Peningkatan Kesadaran Publik pada Kelompok Usia Produktif di SMAN 4 Sidrap - Akbar Harisa; Abdul Majid; Andi Rahmaniar Suciani Pujiningrum; Nur Syamsu Ismail; Salki Sadmita; Yodang Yodang (Universitas Baiturrahim, 2026)
Dementia is one of the global health problems that affects not only the elderly but also individuals in the productive age group. This condition is known as Young-Onset Dementia (YOD), which can occur before the age of 65 and is often linked to unhealthy lifestyle habits. The lack of public awareness regarding the risk factors and early signs of dementia poses a challenge in prevention efforts. This community service activity aimed to improve the knowledge of students at SMAN 4 Sidrap about the early recognition and prevention of dementia. The methods used included health education sessions, interactive discussions, and the administration of pre-test and post-test questionnaires. The results showed an increase in participants’ knowledge. Among 52 participants, 55.8% were initially in the moderate category, which increased to 73.1% in the good category after the intervention. This activity is expected to serve as an initial step in raising awareness among young people about the importance of maintaining cognitive health and preventing the risk of dementia from an early age